Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0149153
|View full text |Cite
|
Sign up to set email alerts
|

How the Pathogenic Fungus Alternaria alternata Copes with Stress via the Response Regulators SSK1 and SHO1

Abstract: The tangerine pathotype of Alternaria alternata is a necrotrophic fungal pathogen causing brown spot disease on a number of citrus cultivars. To better understand the dynamics of signal regulation leading to oxidative and osmotic stress response and fungal infection on citrus, phenotypic characterization of the yeast SSK1 response regulator homolog was performed. It was determined that SSK1 responds to diverse environmental stimuli and plays a critical role in fungal pathogenesis. Experiments to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…Moreover, similar phenotypic changes have been observed in other fungi26272840, in which the single-gene disruptions increased sensitivity to cell wall damage, high osmolarity, and oxidative stress, as well as showing convoluted colonies. As in other fungi, these results indicated that the CWI and HOG pathways in M. rileyi could functionally overlap in responding to cell wall damage, osmoregulation, and oxidative stress171924.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Moreover, similar phenotypic changes have been observed in other fungi26272840, in which the single-gene disruptions increased sensitivity to cell wall damage, high osmolarity, and oxidative stress, as well as showing convoluted colonies. As in other fungi, these results indicated that the CWI and HOG pathways in M. rileyi could functionally overlap in responding to cell wall damage, osmoregulation, and oxidative stress171924.…”
Section: Discussionsupporting
confidence: 59%
“…Although fungi have mechanisms that guarantee the specificity of MAPK signalling pathways and that insulate other pathways, the pathways respond to many stress in a coordinated manner1719. In some fungi, the HOG and CWI pathways interact in responses the cell wall202122 and oxidative stresses2324.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, similar results for light-regulated genes were published for T. atroviride and Aspergillus nidulans mutants in the tmk3 and sakA genes that code for a mitogen-activated protein kinase (MAPK) orthologous to Hog1p of S. cerevisiae. Importantly, Tmk3 and SakA integrate several stress factors, such as light sensing, stress sensing, and osmosensing (35,36). It is worth noting that in yeast under hyperosmotic stress the repressor Sko1 is phosphorylated by Hog1 and converted to an activator that recruits Hog1 itself as well as the SAGA histone acetyltransferase complex (coactivator) at the promoter of target genes to activate transcription (37).…”
Section: Discussionmentioning
confidence: 99%
“…A . alternata mutant strains lacking the Yap1 transcription activator, the Hog1 mitogen-activated protein (MAP) kinase, the Ssk1 regulator, the Skn7 response regulator, the NADPH oxidase (Nox), or the Gpx3 glutathione peroxidase all displayed hypersensitivity to oxidants and reduced lesion formation on citrus [11,12,1418]. Exogenous addition of iron partially rescued H 2 O 2 sensitivity seen for Yap1 , Hog1 , Skn7 , and Nox mutants [19], indicating the important role of iron uptake in ROS resistance.…”
Section: Introductionmentioning
confidence: 99%